2001
DOI: 10.1046/j.1461-9563.2001.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of five types of trap for woodborers in the Cerambycidae, Buprestidae and Siricidae

Abstract: 1 Traps of four new designs were tested against the conventionally used multiplefunnel trap to determine whether trapping of large wood-boring insects can be improved in western Canada. All four new traps used a large collecting receptacle containing detergent-laced water, and three presented a prominent visual silhouette above the receptacle. 2 In total, 27 336 large woodborers were captured from 10 June to 30 September in an experiment in the southern interior of British Columbia, and 4737 from 6 June to 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 17 publications
3
81
1
1
Order By: Relevance
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…As such they can be considered secondary pests included in the stressed or dead host species categories described by Hanks (1999). Economic damage produced by these species is due to timber degradation caused by larvae boring into the sapwood and heartwood (McIntosh et al 2001;Evans et al 2004). In rare cases, species of Monochamus are known to oviposit in and kill standing coniferous trees following forest disturbances (Gandhi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, some Coleopteran families have received little attention, particularly Buprestidae. The exception is the great number of laboratory and field studies reported on the emerald ash borer (EAB), Agrilus planipennis (Fairnaire) (Coleoptera: Buprestidae), an invasive species originating from Asia that has caused considerable mortality of ash trees in the US and Canada (Bartelt et al, 2007;De Groot et al, 2008;Francese et al, 2008;Lelito et al, 2008;Lelito et al, 2009;Silk et al, 2009;Crook and Mastro, 2010;Silk et al, 2011), and some field experiments to catch different jewel beetles (Montgomery and Wargo, 1983;McIntosh et al, 2001). The black-banded oak borer (BBOB) Coroebus florentinus (Herbst) (Coleoptera: Buprestidae), together with its sister species C. undatus, produce notable damage to cork trees, thereby reducing the production of high quality cork.…”
Section: Introductionmentioning
confidence: 99%